Archaeomagnetic study and thermoluminescence dating of Protobyzantine kilns (Megali Kypsa, North Greece). (June 2015) - Kondopoulou, D.; Aidona, E.; Ioannidis, N.; Polymeris, G.S.; Tsolakis, S.
Abstract: The large Protobyzantine settlement of Megali Kypsa was excavated at the NW part of Chalkidiki peninsula (North Greece). Among the numerous residential buildings a big ceramic complex with twelve kilns was unearthed. Nine of the kilns were preserved fairly well and the archaeological investigation suggested a large ceramic production for local use and exportation. The three best preserved kilns were sampled for an archaeomagnetic study, while numerous TL dating results in combination with archaeological information constrained the last use of the kilns from the end of the 4th to the middle of the 5th century AD. Rock magnetic analyses have been performed on pilot samples and identified magnetite as the main carrier of the natural remanent magnetisation. The samples were subjected to both alternating field and thermal demagnetisation providing reliable directions. Intensities were calculated with the Triaxe protocol and yielded a mean value of 61.2 ± 1.8 μΤ. The obtained results are compared with regional and global geomagnetic field models (SCHA.DIF.3K and ARCH.3K). Our study provides 3 new full-vector data, improving the resolution of the Greek secular variation curve for this poorly documented period.